Konstruksi Nilai Edukatif Dalam Ritual Nyapuh Leger Berdasarkan Landasan Pendidikan Hindu - Ni Putu Gatriyani; I Wayan Jatiyasa (Jurnal Penelitian Agama Hindu, 2026)
Nyapuh Leger is a sacred ritual in Balinese Hindu tradition that serves not only as a purification ceremony but also as a medium for transmitting educational values grounded in local wisdom. However, modernization has gradually diminished younger generations’ understanding of the ritual's philosophical meaning and educational significance. This study aims to analyze the construction of educational values embedded in the Nyapuh Leger ritual from the perspective of the foundations of Hindu education. This study employed a qualitative research design with a descriptive approach. Research participants were selected using purposive sampling and included sulinggih (Hindu priests), dalang (traditional puppeteers), religious leaders, academics, organizing committee members, and ritual participants. The study utilized both primary data obtained from informants and secondary data derived from documents, photographs, scholarly publications, and other relevant literature. Data were collected through participant observation, in-depth interviews, documentation, and literature review. Data analysis followed an interactive model consisting of data reduction, data display, verification, and conclusion drawing, while data trustworthiness was ensured through source and technique triangulation. The findings reveal that the Nyapuh Leger ritual embodies educational values encompassing spiritual, ethical and moral, social, cultural, and religious character dimensions. These values are internalized through self-purification practices, the implementation of Tri Kaya Parisudha teachings, the tradition of ngayah (voluntary communal service), the preservation of the Wayang Nyapuh Leger performance tradition, and the integration of the Hindu teachings of tattwa, susila, and acara. Consequently, the ritual functions as a form of non-formal education that strengthens spiritual awareness, religious character, cultural identity, and the development of Hindu education based on local wisdom in the contemporary era.